The Influence of Business Diversification, Investment Decision and Good Corporate Governance on Firm Performance (An Empirical Study on Companies in The Industrial Sector in ASEAN from 2019 to 2022) - Muhammad Zain Satria Atmaja; Wiwik Utami (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze and test the impact of Business Diversification, Investment Decisions, and Good Corporate Governance on Company Performance. Company performance is measured using Return on Assets (ROA), while the independent variables include Business Line, Asset Growth, and Institutional Ownership, with Company Size as a control variable. The research population consists of industrial sector companies listed on the Indonesia Stock Exchange, Singapore, Malaysia, Thailand, and the Philippines during the period of 2019-2022. The sample size was calculated using the Slovin formula, resulting in 95 companies, with 19 companies selected from each country (quota random sampling), totaling 380 data points for analysis. Data analysis was conducted using multiple linear regression with the aid of Eviews 12 statistical software. The results show that Business Diversification, Investment Decisions, and Institutional Ownership have a positive and significant impact on Return on Assets. Analysis for each ASEAN country concluded that business diversification does not have a significant effect in Indonesia, investment decisions do not have a significant effect in Malaysia, and Institutional Ownership does not have a significant effect in Thailand.